Reaching for Gold! The Impact of a Positive Reputation Shock on Career Choice - Daniel Goller; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze the causal influence a positive reputation shock for a particular occupation may have on career choice. The measure of the positive reputation shock is the unpredictable event that a young adult from one's own country wins a (gold) medal in a particular occupation at the World Skills—the world championship of vocational skills. In an occupation with a gold medal won, searches for apprenticeship vacancies increase significantly by around 7 percent compared to occupations that do not win a competition. In occupations where only a silver or bronze medal is awarded, the effect is also positive and statistically significant, but less pronounced. More importantly, the increase in searches for apprenticeship vacancies in the current year has also led to around 2.5 percent more contracts being signed in the winning occupation, and there are indications that these apprenticeships have a better match between employers and employees (trainees).
Keywords: I21; J22; J24; 330; role models; reputation shock; career choice; labor supply; apprenticeship